A novel silver(i)-Keggin-polyoxometalate inorganic–organic hybrid: a Lewis acid catalyst for cyanosilylation reaction1. Issue 31 (21st August 2015) - Hu, Tuo-Ping; Zhao, Ya-Qin; Mei, Kai; Lin, Shu-Jie; Wang, Xing-Po; Sun, Di
<x xml:space="preserve">Abstract</x> A novel polyoxometalate (POM) hybrid material based on a Keggin polyanion and silver(i)–organic sheets, namely, [Ag4(apym)4(SiW12O40)]n (1), where apym = 2-aminopyrimidine, has been synthesized under hydrothermal conditions.